Play therapy in perspective theory of eco systemic therapy - Sofwan Adiputra; Mujiyati Mujiyati (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
Play therapy is a counseling approach for children applying toys, games, and otherplay media to communicate to the children "language." One of the Play therapy models that combine ecosystems as being formed by an inseparable reciprocal relationship between living things, and their environment is Eco systemic Play Therapy (EPT). Ecosystem Play Therapy as a hybrid model that integrates the concepts of science biology, several models of child psychotherapy, and developmental theories. This model is not eclectic. Rather, it is the integration of several models to create an independent model that is different from the sum ofits parts. The focus of EPT is on the process of optimizing the implementation of the child's function as the context of the child's ecosystem or world. EPT is developed from a phenomenological philosophical perspective, in contrast to traditional perspectives.